Lessons from vernacular architecture - Weber, Willi; Yannas, Simos (2014)
"The architectural community has had a strong and continuing interest in traditional and vernacular architecture. This has been rekindled by the need to develop an architecture that works with climate, rather than against it, to create more sustainable buildings. Most earlier research and existing publications on traditional or vernacular architecture have followed an anthropological or archaeological approach, whereas books on climatic design and sustainable architecture tend to refer to contemporary principles and built precedents without direct reference to past experience. Lessons from Traditional Architecture takes lessons directly from traditional and vernacular architecture and offers them to the reader as guidance and inspiration for new buildings. The appropriate technical and social solutions provided by vernacular and traditional architecture are analysed in detail. International case studies focus on environmental design aspects of traditional architecture in a broad range of climatic conditions and building types"--
Bioclimatic Facets of Vernacular Architecture -- Vernacular Architecture as Model.
Includes bibliographical references and index.
Keywords: Sustainable architecture; Vernacular architecture -- Environmental aspects; ARCHITECTURE / Sustainability & Green Design